Micro-RNA Analysis of Pancreatic Cyst Fluid for Diagnosing Malignant Transformation of Intraductal Papillary Mucinous Neoplasm by Comparing Intraductal Papillary Mucinous Adenoma and Carcinoma - Yohei Shirakami (Journal of Clinical Medicine, 2021)
Although intraductal papillary mucinous neoplasm (IPMN) is thought to be a precursor lesion of pancreatic cancer, diagnosing malignant transformation of IPMN using non-invasive diagnostic methods is difficult and complicated. Micro-RNAs (miRNAs) are currently recognized as biomarkers and molecular targets of various diseases, including malignancy. In this study, we investigated a potential diagnostic approach using miRNA in pancreatic cyst fluid as a marker for evaluating malignant alternation of IPMN. Cystic fluid was sampled mainly during surgical resection. The collected samples were evaluated by performing comprehensive analysis of miRNA using a highly sensitive DNA chip. miRNA expression was compared between IPM adenoma (IPMA) and IPM carcinoma (IPMC) to evaluate the related biomarkers for malignant transformation of IPMN. miRNA analysis revealed that six miRNAs (miR-711, miR-3679-5p, miR-6126, miR-6780b-5p, miR-6798-5p, and miR-6879-5p) in IPMC were significantly enriched compared to those in IPMA. The difference was validated using quantitative real-time PCR. Cyst fluid miRNA analysis might be useful for diagnosing malignant alteration of IPMN. Further evaluations of diagnostic capability as well as functional analysis using the identified miRNAs are required with larger cohorts to confirm its efficacy.